PENGARUH PERTUMBUHAN EKONOMI, JUMLAH ANGKATAN KERJA, DAN TINGKAT UPAH TERHADAP PENYERAPAN TENAGA KERJA PROVINSI BALI - Wiasih, Ni Komang Pande; Karmini, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.12.TAHUN.2021DO - 10.24843/EEB.2021.v10.i12.p05, 2021)
The condition of labor absorption shows that the higher the unemployment rate, the higher the poverty, crime, and socio-economic phenomena in society. Absorption of labor is one of the supporters of economic development carried out by developing countries and has the aim, among others, to create equitable economic development. This study aims: 1) To determine the effect of economic growth, the number of the workforce, and the wage level simultaneously on the absorption of district/city workers in the Province of Bali; 2) To determine the effect of economic growth, the number of labor force, and the partial wage level on the absorption of labor in districts/cities in Bali Province. The data used is secondary data from 2010 – 2019 with quantitative and qualitative data types, then the data is processed using multiple linear regression analysis techniques. The results of this study indicate that: 1) Economic growth, the number of labor force, and the level of wages simultaneously affect the absorption of labor; 2) Partially, economic growth has no effect on employment. The number of labor force and the wage level partially have a positive and significant effect on labor absorption.